A Genome-Wide Association Study Identifies New Loci Involved in Wound-Induced Lateral Root Formation in Arabidopsis thaliana - Justamante, María Salud; Ibáñez, Sergio; Peidró, Adrián; Pérez-Pérez, José Manuel (Frontiers in Plant Science, 2019)
Root systems can display variable architectures that contribute to nutrient foraging or to increase the tolerance of abiotic stress conditions. Root tip excision promotes the developmental progression of previously specified lateral roots (LRs), which allows to easily measuring the branching capacity of a given root as regards its genotype and/or growth conditions. Here, we describe the natural variation among 120 Arabidopsis thaliana accessions in root system architecture (RSA) after root tip excision. Wound-induced changes in RSA were associated with 19 genomic loci using genome-wide association mapping. Three candidate loci associated with wound-induced LR formation were investigated. Sequence variation in the hypothetical protein encoded by the At4g01090 gene affected wound-induced LR development and its loss-of-function mutants displayed a reduced number of LRs after root tip excision. Changes in a histidine phosphotransfer protein putatively involved in cytokinin signaling were significantly associated with LR number variation after root tip excision. Our results provide a better understanding of some of the genetic components involved in LR capacity variation among accessions.